2022
DOI: 10.1007/s12144-021-02641-3
|View full text |Cite
|
Sign up to set email alerts
|

Online risky behavior and sleep quality among Chinese college students: The chain mediating role of rumination and anxiety

Abstract: This study explored the chain mediating effects of rumination and anxiety in the relationship between online risky behavior and sleep quality among Chinese college students. A sample of 1039 Chinese college students (Mage = 19.49, SD = 1.14, 53.32% males) were investigated with Online Risky Behavior Scale (ORBS), Pittsburgh Sleep Quality Index scale (PSQI), Ruminative Responses Scale (RRS) and Self-rating Anxiety Scale (SAS). The results showed that: (1) There is a significant positive correlation among online… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 67 publications
2
3
0
Order By: Relevance
“…Correlation analysis between GD, rumination and sleep quality was consistent with previous findings which reported online risky behavior (e.g., excessive gaming) was positively associated with rumination and sleep quality, and indirectly impacted on sleep quality through the mediation of rumination and anxiety (64).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Correlation analysis between GD, rumination and sleep quality was consistent with previous findings which reported online risky behavior (e.g., excessive gaming) was positively associated with rumination and sleep quality, and indirectly impacted on sleep quality through the mediation of rumination and anxiety (64).…”
Section: Discussionsupporting
confidence: 90%
“…The USM factor has been found to have a weaker correlation with the total PSQI than other factors among Chinese individuals without insomnia (75,76). Some studies have found that online risky behaviors and internet (64,91). Therefore, further research examining the relationship between GD and sleep quality is needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the Cronbach's α coefficient was 0.78. Similar values were found in other research with non-clinical Chinese samples (Qiu et al, 2022).…”
Section: Methodssupporting
confidence: 92%
“…The results indicated that other psychological mechanisms might contribute to the impacts of hypercompetitive attitude and interpersonal security on sleep quality. Concerning the direct effect of hypercompetitive attitude on sleep quality, previous research has indicated that individuals with hypercompetitive attitudes easily generate high levels of stress, hostility, rumination and distress [ 9 , 47 , 48 ], which had negative impacts on sleep quality [ 42 , 49 , 50 , 51 , 52 ]. Besides the mediating effect of anxiety between interpersonal security and sleep quality, previous studies have also noted that depression could mediate the association between aversive social relationships and poor sleep quality [ 53 ].…”
Section: Discussionmentioning
confidence: 99%